Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd008324
|View full text |Cite
|
Sign up to set email alerts
|

Psychological therapies versus antidepressant medication, alone and in combination for depression in children and adolescents

Abstract: Analysis 4.3. Comparison 4 Combination therapy versus psychological therapy plus placebo, Outcome 3 Remission by cutoff (post-intervention).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Follow-up studies of both pharmacotherapy and psychotherapy randomized controlled trials (RCTs) show that 25–50% of the depressed adolescents relapse within 6 months to 2 years post-treatment (March and Vitiello, 2009). A recent Cochrane meta-analysis concluded that there is very limited evidence demonstrating the relative effectiveness of antidepressant medication, psychological interventions, and a combination of these interventions in depressed youth (Cox et al, 2012). However, despite the fact that pharmacological treatments of mild to moderate adolescent MDD have not shown significant treatment effects and may introduce both short- and potential long-term negative side effects (Hetrick et al, 2007; Adegbite-Adeniyi et al, 2012), 14.1% of adolescents with primary mood disorders are treated with antidepressant medication in the U.S. (Merikangas et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up studies of both pharmacotherapy and psychotherapy randomized controlled trials (RCTs) show that 25–50% of the depressed adolescents relapse within 6 months to 2 years post-treatment (March and Vitiello, 2009). A recent Cochrane meta-analysis concluded that there is very limited evidence demonstrating the relative effectiveness of antidepressant medication, psychological interventions, and a combination of these interventions in depressed youth (Cox et al, 2012). However, despite the fact that pharmacological treatments of mild to moderate adolescent MDD have not shown significant treatment effects and may introduce both short- and potential long-term negative side effects (Hetrick et al, 2007; Adegbite-Adeniyi et al, 2012), 14.1% of adolescents with primary mood disorders are treated with antidepressant medication in the U.S. (Merikangas et al, 2013).…”
Section: Introductionmentioning
confidence: 99%